Analysis of Emission Infrared Spectra of Protein Solutions in Low Concentrations - Penkov, Nikita; Penkova, Nadezda (Frontiers in Physics, 2020)
In this work, based on the method of infrared emission spectroscopy, the study of emission spectra of interferon-gamma (IFNγ) solution in a mixture or surrounded by three low-concentration solutions (IFNγ, antibodies to IFNγ, glycine buffer) or water control was performed. First of all, the solutions of low concentrations themselves were studied. It was shown that low-concentration solutions of IFNγ and antibodies to IFNγ had lower emission intensity in three spectral bands near 800, 1300 and 2000 cm-1 compared to water control. Glycine buffer solution had a radiation level indistinguishable from that of the control. In this work, the effect of adding these low-concentration solutions to IFNγ (1 mg/mL) was compared to the effect of adding water control to IFNγ. All solutions or water were added in 10% (v/v). It was found that adding each of the three test solutions induced an increase in the radiation intensity of the IFNγ solution in the spectral range of 400-1700 cm-1 (compared to the IFNγ solution with control spike). It was also tested whether the radiation of the studied low-concentration solutions surrounding the IFNγ solution (1 mg/mL) affected the IFNγ radiation. The measurement results were compared to the data obtained for IFNγ surrounded by water control. All three solutions were found to exert a distant effect on the IFNγ solution (1 mg/mL), which was manifested in a decrease in the intensity of its radiation near 1000 and 1500 cm-1 compared to the control solution of IFNγ. Thus, the emission spectra of low-concentration aqueous solutions were measured for the first time, and differences in the emission spectra of the IFNγ solution depending on low-concentration additives and the environment were shown. The paper interprets the observed differences and discusses possible mechanisms underlying the observed phenomena.